Effect of the Ligand Backbone on the Reactivity and Mechanistic Paradigm of Non‐Heme Iron(IV)‐Oxo during Olefin Epoxidation. (7th May 2021) - Biswas, Jyoti Prasad; Ansari, Mursaleem; Paik, Aniruddha; Sasmal, Sheuli; Paul, Sabarni; Rana, Sujoy; Rajaraman, Gopalan; Maiti, Debabrata
Abstract: The oxygen atom transfer (OAT) reactivity of the non‐heme [Fe IV (2PyN2Q)(O)] 2+ (2 ) containing the sterically bulky quinoline‐pyridine pentadentate ligand (2PyN2Q) has been thoroughly studied with different olefins. The ferryl‐oxo complex 2 shows excellent OAT reactivity during epoxidations. The steric encumbrance and electronic effect of the ligand influence the mechanistic shuttle between OAT pathway I and isomerization pathway II (during the reaction stereo pure olefins), resulting in a mixture of cis ‐ trans epoxide products. In contrast, the sterically less hindered and electronically different [Fe IV (N4Py)(O)] 2+ (1 ) provides only cis ‐stilbene epoxide. A Hammett study suggests the role of dominant inductive electronic along with minor resonance effect during electron transfer from olefin to 2 in the rate‐limiting step. Additionally, a computational study supports the involvement of stepwise pathways during olefin epoxidation. The ferryl bend due to the bulkier ligand incorporation leads to destabilization of both d z 2 and d x 2 - y 2 orbitals, leading to a very small quintet–triplet gap and enhanced reactivity for 2 compared to 1 . Thus, the present study unveils the role of steric and electronic effects of the ligand towards mechanistic modification during olefin epoxidation Abstract : The steric and electronic effects exerted by the bulky quinoline‐pyridine pentadentate ligand (2PyN2Q) in the non‐heme complex [Fe IV (2PyN2Q)(O)] 2+ play a key role in olefin epoxidation by oxygen atom transfer and trigger mechanistic diversification. In the present study, the mechanism of olefin epoxidation was thoroughly investigated and rationalized with a detailed computational study.